Job Seekers Perception on Green Employer Branding and Corporate Social Responsibility - Niaraki, Soheil Rahimi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The study analyzes the perception of students in their final semester studying at international higher education destinations on the green employer branding and corporate social responsibility. We believe that these job seekers are influenced by the social actions of potential employers and we will test this hypothesis using a statistical model. Data was gathered using a survey in which students reported demographic data about themselves, their perceptions about employer branding, the importance they placed on corporate social responsibility and other factors such as their views on the free market, their political engagement. The survey instrument combines measures from (Klimkiewicz & Oltra, 2017) and (Jost et al., 2003) A total of 101 respondents completed the questionnaire. The respondents were graduating or recent graduates from international higher education locations such as EMU and other universities across Europe. The relationship between perception towards CSR was analyzed by gender, work experience and the generation they are part of. The theoretical framework was established by conducting a thorough literature review using academic articles, books, journals, statistical information and prior studies on green employer branding and job seekers perspective on green employer branding. The data analysis and hypothesis testing was carried out using JAMOVI statistical software. Promoting a greener environment is a major goal for many businesses today, consequently findings from this study can help companies and managers improve their employer branding in line with this goal. International higher education institutions are faced with the expectation to contribute to the employability of their graduates and they can benefit from understanding the attitudes of students towards employer attractiveness and corporate social responsibility.

ÖZ: Çalışma uluslararası yüksek öğrenim kurumlarında son döneminde olan veya yeni mezun olmuş olan üniversite öğrencilerinin yeşil işveren markası ve kurumsal sosyal sorumlulukları ile ilgili algılarını incelemektedir. İş arayanların potansiyel iş başvurusu yaparken işverenlerin sosyal davranışlarından etkilendiklerine inanmaktayız ve bu çalışmada bu hipotezi istatistiksel bir model ile test etmekteyiz. Çalışmada kullanılan veriler öğrencilerin demografik bilgileri, işveren markası algıları, kurumsal sorumluluğa verdikleri önem, serbest piyasa sistemi ile ilgili görüşleri, siyasi etkinlikleri ile ilgili cevapladıkları bir anket ile toplanmıştır. Anket sorularının hazırlanmasında literatürde önceden geliştirilmiş ölçeklerden faydalanılmıştır. Toplam 101 katılımcı anketi cevaplamıştır. Katılımcılar DAÜ ve Avrupa’da çeşitli üniversitelerde mezuniyete yakın veya yeni mezun olmuş öğrencilerden oluşmuştur. Kurumsal sosyal sorumluluk ile ilgili görüşler ile cinsiyet, çalışma tecrübesi ve katılımcı yaşı arasında olası ilişkiler incelenmiştir. Kuramsal çerçeve literatür taraması ile oluşturulmuş ve mevcut akademik makale, kitaplarda yeşil işveren markası, iş arayanların önem verdiği unsurlar ile ilgili daha önce yapılan çalışmaların bulguları ile oluşturulan kuramsal öğretilerden yararlanılmıştır. Veri analizi için JAMOVI istatistik programı kullanılmıştır. Yeşil bir çevreye katıkıda bulunmak günümüzde birçok işletme için önemli bir hedef olarak görülmektedir. Bu çalışmanın buluguları kurumların işveren markalarını bu hedef doğrultusunda oluşturmasına katkıda bulunabilecektir. Uluslararası yüksek öğretim kurumları için mezunlarının iş bulabilmesi önemli bir beklentidir. Yüksek öğretim kurumlarının öğrenci ve mezunlarının işveren markasında neler aradığını ve kurumsal sosyal sorumluluğa verdikleri önemi daha iyi anlaması gereklidir.
Master of Business Administration. Institute of Graduate Studies and Research. Thesis (M.B.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2021. Supervisor: Prof. Dr. Cem Tanova.
Keywords: Business Administration Department; Employment--Job Seeking; Organizational effectiveness; Employer Branding; Green Employer--Social responsibility of business; Branding (Marketing) Management; Employees--Recruiting; Corporations--Public relations; Employer branding, Employer attractiveness, Corporate social responsibility, Free market